The law and finance of initial coin offerings - GURREA-MARTINEZ, Aurelio (Institutional Knowledge at Singapore Management University, 2019)
This chapter analyzes the legal and financial aspects of Initial Coin Offerings (ICOs). Section I examines the concept, features, and structure of an ICO. Section II analyzes the different regulatory approaches to deal with ICOs. Section III provides an overview of some of the accounting and financial challenges ICOs generate. Section VI focuses on the corporate governance aspects of ICOs. Section V analyzes how ICOs may raise issues related to money laundering, and how regulators and policymakers can deal with these problems. Section VI provides an overview of the challenges of ICOs from the perspective of privacy law and data protection. Section VII examines how insolvency may affect the issuer and buyer of tokens, and how insolvency jurisdictions should deal with those issues arising in insolvency proceedings involving cryptoassets. Finally, Section VIII discusses the jurisdictional issues arising in ICOs.